TYPES OF WORD FORMATION USED IN THE 16th CHAPTER OF HARRY POTTER AND THE SORCERER’S STONE NOVEL WRITTEN BY J. K. ROWLING - Intan Savira; Fitrawati Fitrawati (English Language and Literature, 2019)
Word formation is the process of creating new words based on the word itself, or the other words. It means the new words can be created by shortens the words itself, combining them to the other words, add affixes to give grammatical information, etc. The aim of this study is to know the types of word formation used in a literary work, in this case, a novel. The object of this study is the 16th chapter of Harry Potter and the Sorcerer’s Stone written by J. K. Rowling. Type of this study is descriptive. The data were analyzed by using O’Grady & Archibald theory about word formation. The result shows that there were 340 words with the frequency 755 times have word formation process. Inflection (64.1%) becomes the most frequently used, and compounding (4.5%) becomes the less frequently used.